THE ANALYSIS OF COMMON GRAMMATICAL ERRORS IN WRITING NARRATIVE ESSAY OF ENGLISH STUDY PROGRAM STUDENTS AT JAMBI UNIVERSITY - Reni Heryanti; Muhammad Hadi Sucipto; Makmur Makmur (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2017)
The purpose of this quantitative research is to reveal common grammatical errors in writing narrative essay of English Study Program students at Jambi University. The data were collected through writing test. The data were analyzed by using format error identification. This research reveals twelve errors. They were verb-tense, punctuation, capital letters, word choice, spelling, preposition, pronoun, pluralism, redundancy, word order, article, and possessive case. There were 599 errors happened in students’ papers, and the highest amount of error occurred in verb-tense category. There were 303 verb-tense errors (50.58%). Meanwhile, the smallest number of error occurred in article and possessive case category. Both have the same frequency and percentage, which are 6 errors (1.00%) in article and 6 errors (1.00%) in possessive case. The researcher concluded that students made errors because of the lack of grammatical knowledge. Their native language also still influenced the students, which is Bahasa that lead them to made errors.